Predicting postoperative systolic dysfunction in mitral regurgitation: CT vs. echocardiography - Reddy, Prajwal; Anand, Vidhu; Rajiah, Prabhakar; Larson, Nicholas B.; Bird, Jared; Williams, James M.; Williamson, Eric E.; Nishimura, Rick A.; Crestanello, Juan A.; Arghami, Arman; Collins, Jeremy D.; Bratt, Alex (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Volume overload from mitral regurgitation can result in left ventricular systolic dysfunction. To prevent this, it is essential to operate before irreversible dysfunction occurs, but the optimal timing of intervention remains unclear. Current echocardiographic guidelines are based on 2D linear measurement thresholds only. We compared volumetric CT-based and 2D echocardiographic indices of LV size and function as predictors of post-operative systolic dysfunction following mitral repair. Methods: We retrospectively identified patients with primary mitral valve regurgitation who underwent repair between 2005 and 2021. Several indices of LV size and function measured on preoperative cardiac CT were compared with 2D echocardiography in predicting post-operative LV systolic dysfunction (LVEFecho < 50%). Area under the curve (AUC) was the primary metric of predictive performance. Results: A total of 243 patients were included (mean age 57 ± 12 years; 65 females). The most effective CT-based predictors of post-operative LV systolic dysfunction were ejection fraction (LVEFCT; AUC 0.84 [95% CI: 0.77-0.92]) and LV end systolic volume indexed to body surface area (LVESViCT; AUC 0.88 [0.82-0.95]). The best echocardiographic predictors were LVEFecho (AUC 0.70 [0.58-0.82]) and LVESDecho (AUC 0.79 [0.70-0.89]). LVEFCT was a significantly better predictor of post-operative LV systolic dysfunction than LVEFecho (p = 0.02) and LVESViCT was a significantly better predictor than LVESDecho (p = 0.03). Ejection fraction measured by CT demonstrated significantly greater reproducibility than echocardiography. Discussion: CT-based volumetric measurements may be superior to established 2D echocardiographic parameters for predicting LV systolic dysfunction following mitral valve repair. Validation with prospective study is warranted.